Anthropometric differences between race walkers and marathon runners: A cross sectional study (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the present study was to assess anthropometric and body physiological differences in walk racers and marathon runners. Total sixty athletes were selected, further the athletes were divided in to two group i.e. walk racers group (N=30) and marathon runners group (N=30) their aged ranged from 20 to 27 years. The subjects were selected from Punjab, who have participated in either in interuniversity or represented in National. The guidelines issued by International Society for the Advancement of Kinanthropometry (ISAK) were followed for Anthropometric measurements. To test the significant difference of selected physiological and anthropometric variables between walk racer and marathon runners, independent T-test method was employed. The level of significance chosen to test the hypotheses will be 0.05, P < 0.05.Statistical significant differences found in certain anthropometric characteristics in walk racers and marathon runner. The results indicate walk racers have greater leg and foot length, have more calf circumferences than marathon runners.